OVERVIEW OF MAMMOGRAPHY IN GOIÁS BETWEEN 2016 AND 2021 - Silva, Kallyta Myllena e; Silva, Micaellem Rodrigues Santos da; Costa, Wanessa Rocha; Soares, Leonardo Ribeiro (Mastology, 2026)
Objective: This study described the clinical-epidemiological characteristics of women undergoing mammography in the State of Goiás from 2016 to 2021. Methods: This is a cross-sectional, ecological study of women who underwent mammography between 2016 and 2021 in the state of Goiás. The DATASUS database of the Cancer Information System (SISCAN) was used, where age group, municipality of residence, and clinical indication were applied for analysis. Results: Between 2016 and 2021, in Goiás, 451,589 mammograms were performed on women aged 9 to over 79 years, with an average of 75,265 mammograms per year. In 2019, 89,868 procedures were performed, which was the highest number recorded in the analyzed period. In contrast, 2020 had lower demand, totaling 50,263 mammograms. As for the clinical indication, of the 365,152 requested mammograms, 354,370 aimed at screening, mainly for the high-risk population that includes women with a family history of breast cancer, representing 8,617 examinations. In addition, 13,853 mammograms had a diagnostic objective based on suspicious clinical findings, and 5,432 patients underwent mammography for previous treatment of breast cancer. The age group that most underwent mammograms was 50–54 years, totaling 17.3% of the total. In Goiânia, the rate of mammography performed, from 10 to 79 years old, was 4.8% and São João da Paraúna registered the highest rate with 20.5%. Goiânia, Aparecida de Goiás, and Anápolis lead the ranking of mammograms performed, representing 53% of the procedures performed in the state. Conclusion: Through the analysis, it is possible to infer that there is a disproportionate distribution of health resources in the territory of Goiás. In addition, the reduction in the number of mammograms in 2020 is correlated with the COVID-19 pandemic, allowing the loss of early diagnoses in many women, thus contributing to an unfavorable prognosis in the future.